The Potential Disparity in Judicial Pardon Decisions: Formulation Issues in The National Criminal Code - Aji, Muhammad Kharisma Bayu; Istiqomah, Milda; Astiti, Sriti Hesti; Taqwa, Faisal Akbaruddin (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
This scientific article discusses the problems and ideal formulation of judicial forgiveness in the future in Article 54, Paragraph (2) of Law Number 1 of 2023 on the Criminal Code. This article regulates judicial forgiveness but does not explain the requirements, resulting in different interpretations and decision disparities. This research is normative research with a descriptive research nature. The legislative and comparative approaches are used. This study found that the formulation of judicial forgiveness has problems such as abstract norms, alternative requirements, and difficulties when the victim does not forgive the defendant. The ideal formulation of judicial forgiveness is to determine the maximum criminal sanctions and cumulative requirements. The requirement for the lightness of the act can be interpreted as a maximum fine of Category II (IDR 10,000,000.00) and is related to minor crimes in the Criminal Procedure Code. The requirement for the offender’s personal circumstances is linked to Article 22 of the National Criminal Code, and the requirement for the circumstances at the time the crime was committed is linked to the sentencing guidelines in Article 54 paragraph (1) of the National Criminal Code letters b, d, e, f, and j.